Transforming Community: Opportunities for Transdisciplinary Application - Lommerse, Marina; Smith, Dianne; Tiwari, Reena (Springer, 2014)
This chapter discusses how individual authors in Parts I and II of this book have understood and investigated the idea of community. We look at whether and how their definition of community is dependent on location and the nature of their projects, how their views changed through reflection and interaction with community members, and what constitutes capacity building in different socio-cultural contexts. The projects discussed capture a multitude of ways to interface and interact with communities, of modes of interaction, empowerment or engagement, of varying scales and complexity and socio-economic circumstances, as well as of physical locations across the world. The transformative experience is valid, not only for local users/residents in the project, but also for the associated civil society, the policymakers, the professionals, the students and other social actors involved. The case studies described in the chapters in Parts I and II are reflected on in terms of the concept of community as a discipline in its own right, which builds capacity in a transformative experience that brings physical, social, economic or environmental change. We revisit notions of co-creation, capacity building and transformation, and identify transdisciplinary understandings of community engagement. The editors have arrived at the notion of community as a discipline and the increased value of recognizing community engagement as a transdisciplinary practice.